2021
DOI: 10.1038/s41366-021-00999-9
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue prevents glucose intolerance and cardiac remodeling in high-fat-fed mice after a mild myocardial infarction

Abstract: Background Obesity increases the risk of developing impaired glucose tolerance (IGT) and type 2 diabetes (T2D) after myocardial infarction (MI). Brown adipose tissue (BAT) is important to combat obesity and T2D, and increasing BAT mass by transplantation improves glucose metabolism and cardiac function. The objective of this study was to determine if BAT had a protective effect on glucose tolerance and cardiac function in high-fat diet (HFD) fed mice subjected to a mild MI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
(90 reference statements)
1
7
0
Order By: Relevance
“…Accumulating preclinical evidence suggests an inverse relationship between BAT activity and pathological cardiac hypertrophy and HF. [16][17][18][19][20][21][22] This is further supported by recent clinical observations showing individuals with active BAT have lower risk of adverse cardiac events and decreased prevalence of HF. 5,11 However, the effect of BAT on the initial responses of hypertrophic signaling and cardiac metabolic remodeling during the induction of pathological stress has not been previously addressed.…”
Section: Discussionsupporting
confidence: 56%
“…Accumulating preclinical evidence suggests an inverse relationship between BAT activity and pathological cardiac hypertrophy and HF. [16][17][18][19][20][21][22] This is further supported by recent clinical observations showing individuals with active BAT have lower risk of adverse cardiac events and decreased prevalence of HF. 5,11 However, the effect of BAT on the initial responses of hypertrophic signaling and cardiac metabolic remodeling during the induction of pathological stress has not been previously addressed.…”
Section: Discussionsupporting
confidence: 56%
“…However, in male mice, the epididymal WAT (eWAT) is the unique depot prone to inflammation and obesogenic remodeling [10,11]. The interscapular AT depot, called brown AT (iBAT), is fundamental for combating obesity and diabetes, favoring cardiac remodeling after mild infarction in mice [12]. The main histological fingerprint of pro-inflammatory changes in AT depots is the crown-like structure (CLS), a peculiar arrangement of infiltrating macrophages around dying adipocytes [13].…”
Section: Of 19mentioning
confidence: 99%
“…Beyond fighting obesity writ large, one could envision specific uses for brown fat—for example, as an infusion that protects heart attack victims from frequent after-effects that include developing type 2 diabetes or impaired heart functioning. A 2021 study found that mice fed a high-fat diet and then induced to have a heart attack had a better ability to process glucose and to exercise strenuously if they had received a prophylactic brown fat infusion soon after the heart attack ( 4 ). What’s more, compared with control mice, those who had received brown fat did not experience a common warning sign of coronary artery disease: an increase in the mass of the heart’s left ventricle.…”
Section: Key Transformationmentioning
confidence: 99%